2014
DOI: 10.1186/1752-1947-8-238
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular angioleiomyoma of the knee with an atypical finding on gadolinium-enhanced magnetic resonance imaging: a case report

Abstract: IntroductionAngioleiomyoma is a benign smooth muscle tumor. It originates in the tunica media of veins. In general, it arises from the dermis, subcutaneous fat and fascia of lower extremities in middle-aged women. The case of intra-articular occurrence is very rare.Case presentationThis case report describes a 30-year-old Asian man with a 6-month history of recurrent pain localized in the lateral side of his left knee. Magnetic resonance imaging revealed an isolated intra-articular lesion. We performed a surgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Angioleiomyoma can occur anywhere in the body and is most often seen in the extremities, particularly the lower limbs [ 8 ], but very rare in the knee joint. Al-Jabri et al reported a case of an angioleiomyoma presented with recurrent pain and a soft tissue swelling at the posteromedial aspect of right knee [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Angioleiomyoma can occur anywhere in the body and is most often seen in the extremities, particularly the lower limbs [ 8 ], but very rare in the knee joint. Al-Jabri et al reported a case of an angioleiomyoma presented with recurrent pain and a soft tissue swelling at the posteromedial aspect of right knee [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of angioleiomyoma is estimated about 5% among all soft tissue tumors with the lower limbs being most commonly affected [2]. However, the presence of the neoplasm at the knee joint is very rare and only few cases are reported in the literature [6,7,8,9,10,11,12]. Its clinical appearance seems more common in middle-aged people with females being affected almost twice as often [2,8,13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%